Brexpiprazole and cariprazine: distinguishing two new atypical antipsychotics from the original dopamine stabilizer aripiprazole - Frankel, Joshua S. (Ther Adv Psychopharmacol, 2016)
BACKGROUND: Brexpiprazole and cariprazine are the latest US Food and Drug Administration approved atypical antipsychotics available in the United States. Both function as partial agonists of the dopamine-2 receptor (D(2)R), a mechanism of action shared with aripiprazole. However, all three differ in their affinities for the D(2)R as well as for serotonin receptors (5-HTRs). This paper seeks to delineate these pharmacodynamic and clinical differences amongst the three dopamine partial agonist atypical antipsychotic drugs. METHODS: PubMed and clinicaltrials.gov searches were used to generate preclinical and clinical evidence for review. Data derived from animal models and human subjects were used to provide insight on clinical mechanisms and adverse effect potentials. Clinical trial data were reviewed to compare clinical efficacy and adverse effects. RESULTS: Efficacies among the three drugs are comparable for their shared indications. Side-effect profile and underlying pharmacodynamic mechanism of action for each drug may differ. CONCLUSION: Partial agonism of the D(2)R is a similarity of the three drugs reviewed. Each drug varies in affinity for both the D(2)R and a diverse group of 5-HTRs, generating a distinct profile of clinical indications and adverse effects for each.